Effects of ovariectomy and estrogen treatment on learning and hippocampal neurotransmitters in mice - Heikkinen, Taneli; Puoliväli, Jukka; Liu, Li; Rissanen, Anna; Tanila, Heikki (My University, 2002)
This study examined the effects of long-term estrogen treatment (sc 17β-estradiol minipellets) on learning in C57BL/6J female and male mice using a position discrimination task in the T-maze and a win-stay task (1/8 arms baited) in the radial arm maze (RAM). In addition, hippocampal monoamines and ChAT activity were measured at the end of the study and correlated to task performance. Female sham-operated (gonadally intact) and ovariectomized (OVX) mice were treated with estrogen either for 7 or 40 days before the behavioral tests and intact male mice for 7 days before the behavioral tests. In sham-operated mice the 40-day estrogen treatment improved RAM performance and in OVX mice both the 7- and 40-day estrogen treatments improved the performance in both maze tasks. The estrogen treatment also improved RAM performance in males. The hippocampal ChAT, NA, 5-HIAA, and DOPAC levels were decreased in OVX mice. Furthermore, the effects of estrogen treatment on the levels of hippocampal 5-HT and its metabolite 5-HIAA were different in sham-operated than in OVX mice. We could find no correlation between cognitive measures and neurochemical variables. This study gives new information about the effects of estrogen on learning and hippocampal neurotransmitters in mice.
Keywords: mice; estrogen; ovariectomy; radial arm maze; T-maze; learning; monoamines; choline acetyltransferase; hippocampus; striatum